Pengaruh Kualitas Produk, Harga Dan Promosi Terhahadap Keputusan Pembelian Minuman Nu Greantea - Nur Adzkia Nabila; Suadi Sapta Putra; Kumba Digdowiseiso Digdowiseiso (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to analyze how much influence product quality, price and promotion have on purchasing decisions. This type of research uses a quantitative descriptive method. The information collection method that was tried was using a closed questionnaire to 100 respondents assisted by using the SPSS version 26 program to get the results of the decision to buy nu greantea drinks. The results of the analysis in this study prove that each variable has a significant influence on the dependent variable, namely purchasing decisions. With the results of this study, nu greantea drinks can reach more consumers. Keywords: Product Quality, Price and Promotion, Purchase Decision.